The Strategy For Selecting Institutional Model And Financial Analysis Of Sesame Agroindustry - Luluk Sulistiyo Budi; M. Syamsul Ma’arif; Illah Sailah; Sapta Raharja (Department of Agroindustrial Technology, Bogor Agricultural University, 2009)
Business institution is one of the important components to develop an agroindustry. The aim of this research was to find the appropriate institutional model for sesame agroindustry based on financial feasibility analysis comprises Net Present Value (NPV), Internal Rate of Return (IRR), Pay Back Period (PBP) and Net B/C Ratio. The method to develop strategy was Analytical Hirarchy Process (AHP) approach, while to choose an institution was exponential comparison method (MPE). The results of analysis showed that the main factor in developing strategy of sesame agroindustry based on evaluation value were market demand (0.209), and material quality and availability (0.198). The main actors were bussinessman (0.129) and the local goverment (0.123). The main objective for sesame agroindustrial development was increasing farmer income (0.216). The results of analysis based on aggregate weighting showed that the appropriate development institutions were integrated agroindustrial cooperative pattern (117,106,036) and self-sufficient bussiness pattern (107,560,765). Based on financial analysis, it was known that opportunity level (discount rate) was 20%, NPV was Rp 292,796,108.90, Net B/C was 1.27, IRR 22.04% and PBP was 1.34%. In conclusion, the development of the sesame-based agroindustry with cooperative institutional pattern was feasible. Keyword : strategy, institution, cooperation, sesame agroindustry, financial analysis.